Face Recognition Using Image Processing Techniques: A Survey (International Journal of Engineering and Computer Science, 2014)
Face detection is becoming one of the most interesting topics in the computer vision literature. The survey is conducted to analyze the face recognition techniques and timeline view on different methods to handle general face recognition problems. Image processing techniques focuses on two major tasks such as Improvement of pictorial information for human interpretation and processing of image data for storage, transmission and representation for autonomous machine perception. One of the common fundamental techniques that facilitate natural human-computer interaction (HCI) is face detection. In this paper, the survey is made based on a comparison of the recent advances in face detection using various image processing techniques such as Eigen faces, Hidden Markov Model(HMM), Geometric based algorithm and template matching algorithms. These techniques improve quality, removes noise, versatile in nature, and preserves original data precision of the image.